The British Soldier in the Peninsular War - Daly, G. author. aut Link
XIII, 302 p.
Keywords: Combining military and cultural history, the book explores British soldiers' travels and cross-cultural encounters in Spain and Portugal, 1808-1814. It is the story of how soldiers interacted with the local environment and culture, of their attitudes and behaviour towards the inhabitants, and how they wrote about all this in letters and memoirs.